STRATIFIKASI SOSIAL PADA CERPEN “SENYUM KARYAMIN” KARYA AHMAD TOHARI - Andi Widiono (Kantor Bahasa Lampung, 2017)
AbstractShort story is one of the literary works that presents a story about social stratification. Socialstratification is a picture of human life in a society that is divided into several levels or socialclasses. According to Budiyono, social stratification is divided into three classes, namely upper,middle, and lower. The picture of social stratification is clearly depicted by the characters in thestory. The method used in this research is descriptive qualitative and library research is used as thedata collection technique. The results obtained in this study is that the short story